Non-invasive management of Thandaga vaatham (lumbar spondylosis) through Siddha Varmam therapy - A case report - Shunmugaram Shenbagaraj; Saraswathi Balasubramanian; Deepa Ravichandran; Vinodini Ramamoorthy; Sathiyarajeswaran Parameswaran; Shyamala Rajkumar (Journal of Ayurveda and Integrative Medicine)
A 32-year-old female homemaker came with a complaints of chronic low back pain, radiating to both lower limbs, stiffness especially in the morning difficulty in walking and standing with intensified pain during household chores for two years. She was diagnosed with Tantaka vātam, one of the eighty types of vātam disease which is equivalent to lumbar spondylosis. She was treated with therapeutic Varmam manipulations in every 7 days for a period of 48 days and followed for six months. Oswestry Disability Index, Siddha based diagnostic parameters were used to assess the clinical efficacy and no adverse events were noted during the treatment course and follow up period. This case report has provided a promising non-invasive and cost-effective therapeutic indication for the management of Tantaka vātam (lumbar spondylosis).